2009
DOI: 10.1002/adfm.200801032
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature‐Grown Transition Metal Oxide Based Storage Materials and Oxide Transistors for High‐Density Non‐volatile Memory

Abstract: An effective stacked memory concept utilizing all‐oxide‐based device components for future high‐density nonvolatile stacked structure data storage is developed. GaInZnO (GIZO) thin‐film transistors, grown at room temperature, are integrated with one‐diode (CuO/InZnO)–one‐resistor (NiO) (1D–1R) structure oxide storage node elements, fabricated at room temperature. The low growth temperatures and fabrication methods introduced in this paper allow the demonstration of a stackable memory array as well as integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
122
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(123 citation statements)
references
References 25 publications
1
122
0
Order By: Relevance
“…As a representative amorphous oxide semiconductor (AOS) material, amorphous InGaZnO (a-IGZO) has been studied and developed intensively as an active layer of thin-film transistors (TFTs) for switching/driving devices in flexible e-paper, transparent/lightweight display backplanes for active-matrix liquid crystal display (AMLCD) and/or active-matrix organic light-emitting diode display (AMOLED) [1,2], stackable logic circuitry [3], and 3-D memories [4]. In order to design and integrate various innovative systems using AOS TFTs, the circuit simulation with physics-based and processcontrolled parameters, not fitting parameters, is indispensible for process/structure optimization.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative amorphous oxide semiconductor (AOS) material, amorphous InGaZnO (a-IGZO) has been studied and developed intensively as an active layer of thin-film transistors (TFTs) for switching/driving devices in flexible e-paper, transparent/lightweight display backplanes for active-matrix liquid crystal display (AMLCD) and/or active-matrix organic light-emitting diode display (AMOLED) [1,2], stackable logic circuitry [3], and 3-D memories [4]. In order to design and integrate various innovative systems using AOS TFTs, the circuit simulation with physics-based and processcontrolled parameters, not fitting parameters, is indispensible for process/structure optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, T. Nishijima et al reported the low-power display system through the non-volatile memory (NVM) array [8]. The RRAM devices are next-generation NVM alternative technologies owing to its simple device structure, low power consumption, favorable scalability and fast switching [9,10]. However, to implement high density 4F 2 cross point array, a non-linear selection device such as diode is needed to suppress the sneak current through the unselected cells which causes readout errors.…”
mentioning
confidence: 99%
“…Otherwise M = "1". When three voltage variables are applied to T 1 , T 2 , T 3 respectively, the next states, and its present states S 1 , S 2 are described by (2). The output M and inputs T 1 , T 2 , T 3 , and present states S 1 , S 2 is described by (3).…”
Section: Designs and Simulationsmentioning
confidence: 99%
“…However, sneak path problem limits the size of the arrays and increases their power consumption. To solve the sneak path problem, various solutions were proposed, such as P-N junction type diode [2], Schottky type diode [3], complementary resistive switches (CRS) [4]. Among these proposed solutions, CRS is suitable for reducing parasitic current and making the application of large passive crossbar arrays feasible [4,5].…”
Section: Introductionmentioning
confidence: 99%